If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(2x + -5)(2x + -5) + -1(3x + -7)(5 + -2x) = 0 Reorder the terms: 3(-5 + 2x)(2x + -5) + -1(3x + -7)(5 + -2x) = 0 Reorder the terms: 3(-5 + 2x)(-5 + 2x) + -1(3x + -7)(5 + -2x) = 0 Multiply (-5 + 2x) * (-5 + 2x) 3(-5(-5 + 2x) + 2x * (-5 + 2x)) + -1(3x + -7)(5 + -2x) = 0 3((-5 * -5 + 2x * -5) + 2x * (-5 + 2x)) + -1(3x + -7)(5 + -2x) = 0 3((25 + -10x) + 2x * (-5 + 2x)) + -1(3x + -7)(5 + -2x) = 0 3(25 + -10x + (-5 * 2x + 2x * 2x)) + -1(3x + -7)(5 + -2x) = 0 3(25 + -10x + (-10x + 4x2)) + -1(3x + -7)(5 + -2x) = 0 Combine like terms: -10x + -10x = -20x 3(25 + -20x + 4x2) + -1(3x + -7)(5 + -2x) = 0 (25 * 3 + -20x * 3 + 4x2 * 3) + -1(3x + -7)(5 + -2x) = 0 (75 + -60x + 12x2) + -1(3x + -7)(5 + -2x) = 0 Reorder the terms: 75 + -60x + 12x2 + -1(-7 + 3x)(5 + -2x) = 0 Multiply (-7 + 3x) * (5 + -2x) 75 + -60x + 12x2 + -1(-7(5 + -2x) + 3x * (5 + -2x)) = 0 75 + -60x + 12x2 + -1((5 * -7 + -2x * -7) + 3x * (5 + -2x)) = 0 75 + -60x + 12x2 + -1((-35 + 14x) + 3x * (5 + -2x)) = 0 75 + -60x + 12x2 + -1(-35 + 14x + (5 * 3x + -2x * 3x)) = 0 75 + -60x + 12x2 + -1(-35 + 14x + (15x + -6x2)) = 0 Combine like terms: 14x + 15x = 29x 75 + -60x + 12x2 + -1(-35 + 29x + -6x2) = 0 75 + -60x + 12x2 + (-35 * -1 + 29x * -1 + -6x2 * -1) = 0 75 + -60x + 12x2 + (35 + -29x + 6x2) = 0 Reorder the terms: 75 + 35 + -60x + -29x + 12x2 + 6x2 = 0 Combine like terms: 75 + 35 = 110 110 + -60x + -29x + 12x2 + 6x2 = 0 Combine like terms: -60x + -29x = -89x 110 + -89x + 12x2 + 6x2 = 0 Combine like terms: 12x2 + 6x2 = 18x2 110 + -89x + 18x2 = 0 Solving 110 + -89x + 18x2 = 0 Solving for variable 'x'. Factor a trinomial. (22 + -9x)(5 + -2x) = 0Subproblem 1
Set the factor '(22 + -9x)' equal to zero and attempt to solve: Simplifying 22 + -9x = 0 Solving 22 + -9x = 0 Move all terms containing x to the left, all other terms to the right. Add '-22' to each side of the equation. 22 + -22 + -9x = 0 + -22 Combine like terms: 22 + -22 = 0 0 + -9x = 0 + -22 -9x = 0 + -22 Combine like terms: 0 + -22 = -22 -9x = -22 Divide each side by '-9'. x = 2.444444444 Simplifying x = 2.444444444Subproblem 2
Set the factor '(5 + -2x)' equal to zero and attempt to solve: Simplifying 5 + -2x = 0 Solving 5 + -2x = 0 Move all terms containing x to the left, all other terms to the right. Add '-5' to each side of the equation. 5 + -5 + -2x = 0 + -5 Combine like terms: 5 + -5 = 0 0 + -2x = 0 + -5 -2x = 0 + -5 Combine like terms: 0 + -5 = -5 -2x = -5 Divide each side by '-2'. x = 2.5 Simplifying x = 2.5Solution
x = {2.444444444, 2.5}
| 2(3x+4)=2x+3 | | 2x+4y=156 | | 4x+-56=12 | | 3(2)-5y=10 | | 24=k(5) | | 3(13-4x)=7-16x | | 3(2)-5=10 | | 3(1)-5y=10 | | 3(0)-5y=10 | | 10x-345=12 | | 3(-1)-5y=10 | | 6x+13y=-15 | | 7x-35=6x | | 47x-241=3 | | 3(-2)-5y=10 | | 35x-250=10 | | -3x+-22=8 | | 15q+-4r=62 | | 76x*220=3230 | | 2x/48=3:12 | | 878574868x=8384748372929 | | 6/11y=19 | | 2*(1/10) | | .002=1/x | | (3r^5+5r^2-4)-(-7r^5-3r^2+16)= | | F(x)=(3x-7) | | 3c+2d=8 | | 2y-2=3 | | 3x-2+5=2(5x-4) | | z^3-j=0 | | 7.50x+8y=93.50 | | 4x=0.9 |